1986
DOI: 10.1111/j.1440-1827.1986.tb02254.x
|View full text |Cite
|
Sign up to set email alerts
|

CALCITONIN‐PRODUCING INSULINOMA: An Immunohistochemical and Electron Microscopic Study

Abstract: A pancreatic endocrine tumor measuring 1.5×1.0×1.0 cm in a 67‐year‐old man with recurrent hypoglycemic attacks was examined by immunohistochemistry and electron microscopy. The tumor cells were relatively uniform, and almost all of them were immunoreactive to Insulin. A few calcitoninpositive cells could be identified scattering in tumor cell strands, and the content of calcitonin in the tumor was 85 ng/g wet tissue. Coexistence of insulin and calcitonin in tumor cells was demonstrated by using adjacent semith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Hypercalcitoninemia due to ectopic calcitonin secretion by several types of PNETs, including insulinoma, has been described [28][29][30][31][32][33]; therefore, we measured calcitonin levels even if our patient had no family history of MTC or clinical and laboratory findings consistent with hyperparathyroidism or pheochromocytoma. Moreover, hypercalcitoninemia due to calcitonin-producing insulinoma has been documented in patients with benign thyroid nodules [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Hypercalcitoninemia due to ectopic calcitonin secretion by several types of PNETs, including insulinoma, has been described [28][29][30][31][32][33]; therefore, we measured calcitonin levels even if our patient had no family history of MTC or clinical and laboratory findings consistent with hyperparathyroidism or pheochromocytoma. Moreover, hypercalcitoninemia due to calcitonin-producing insulinoma has been documented in patients with benign thyroid nodules [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…There are some reports in the literature of both operational and non-functioning calcitonin-secreting PanNETs. [7][8][9][10][11][17][18][19][20][21][22][23][24][25][26] The exact incidence of calcitonin expression in these tumours is unknown. Uccela S et al 26 performed a review of the literature and found a predominance of calcitonin-immunoreactive VIPpomas among FPanNETs, contrary to what the authors found in their own study, in which insulinomas predominated.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 There are few reports in the literature of functioning calcitonin-secreting PNETs, and only 5 case reports of calcitonin secreting insulinomas. [7][8][9][10][11] We describe a case of a 72year old man with an insulinoma secreting calcitonin, and perform a review of the related literature.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the large size and the increased proliferative activity of the insulinoma in our patient, an endocrine tumor of uncertain malignant potential with strong immunostaining for both insulin and calcitonin was diagnosed. Interestingly, the few reported insulinomas that showed calcitonin immunostaining have been typically benign tumors (Ooi et al, 1986;Price et al, 1992;Gaulier et al, 1993;Bugalho et al, 1994), which is in contrast with other calcitonin-producing pancreatic neuroendocrine tumors that were often malignant (Fleury et al, 1998;Takahashi et al, 1998). Moreover, metastatic neuroendocrine tumors to the thyroid gland mimicking medullary thyroid carcinoma have also been described (Matias-Guiu et al, 1997;Leboulleux et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that a few insulinomas may secrete not only insulin and C-peptide but also calcitonin (Ooi et al, 1986;Price et al, 1992;Gaulier et al, 1993;Bugalho et al, 1994;Takahashi et al, 1998). However, most of the few reported cases had incomplete data or lack of documentation of the association between raised serum calcitonin concentration and immunohistochemical detection of calcitonin in pancreatic tumors.…”
Section: Introductionmentioning
confidence: 99%